Ontogenetic view on PIVKA-II in the development of prothrombin synthesis in infants - O. G. Ivanko; A. V. Solianik; I. V. Pashchenko (Patologìâ)
The aim of the research was to study the content of PIVKA-II in the blood serum as an integrative measure of latent vitamin K deficiency in breastfed infants aged from the birth to 6 months of life.